2014
DOI: 10.2298/fil1401065h
|View full text |Cite
|
Sign up to set email alerts
|

The residual spectrum and the continuous spectrum of upper triangular operator matrices

Abstract: Let H and K be separable infinite dimensional Hilbert spaces. We denote by M C the 2×2 upper triangular operator matrix acting on H ⊕ K of the form M C = (A C 0 B). For given operators A ∈ B(H) and B ∈ B(K), the sets ∪ C∈B(K ,H) σ r (M C) and ∪ C∈B(K ,H) σ c (M C) are characterized, where σ r (•) and σ c (•) denote the residual spectrum and the continuous spectrum, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Remark 2.19. A description of the set X∈B(K ,H) σ r (M X ) was given in [13] (see (1)). From Theorem 2.12 and Proof.…”
Section: Corollary 211 Let a ∈ B(h) And B ∈ B(kmentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 2.19. A description of the set X∈B(K ,H) σ r (M X ) was given in [13] (see (1)). From Theorem 2.12 and Proof.…”
Section: Corollary 211 Let a ∈ B(h) And B ∈ B(kmentioning
confidence: 99%
“…with an unknown operator X ∈ B(K , H). See, e.g., [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In [5,6,9,10,12,[14][15][16][17][18], the perturbations of different spectra (the spectra, left (right) spectra, point spectra, continuous spectra, residual spectra,• • • ) of M X were discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that for any T ∈ B(H), in [8,16,18,1], we get the implications: a-Weyl's theorem =⇒ Weyl's theorem =⇒ Browder's theorem, a-Weyl's theorem =⇒ a-Browder's theorem =⇒ Browder's theorem. [19,13].) Let A, B, C ∈ B(H).…”
Section: Preliminariesmentioning
confidence: 99%